Higiene oral en niños menores de 5 años: revisión bibliográfica - Jiménez Rojas, Liseth Esthefania (2023)
The childhood stage is fundamental in terms of oral hygiene. During this time, children experience the growth and development of their teeth and gums. It is necessary to maintain healthy oral care habits; teeth are more susceptible to caries and other conditions, so parents must teach them a regular brushing routine, make sure they use fluoridated toothpaste in adequate concentrations, take them to regular check-ups with the dentist in addition to maintaining a balanced diet. This study aimed to provide information on brushing techniques, as well as to analyze the concentration of ppm of fluoride recommended in toothpastes, and describe the recommendations for good oral hygiene in children under five years of age. The present study has a descriptive, bibliographic, and documentary approach. Based on the literature review of 31 articles published in different scientific journals: PubMed, Google Scholar, Scielo, Elsevier, Medi graphic, and books, among other sources, from 2013. In the results, we obtained that the most frequent and effective technique is the Fones Technique, with (54.55%) being the most effective due to its ease of learning. In addition, the most recommended concentration of fluoride ppm was toothpaste with concentrations less than 1000 ppm with a percentage of (60%). Concerning the oral hygiene recommendations, we evidenced that the most frequent and efficient brushing of our teeth twice a day, the same we conduct starting from the eruption of the first tooth (35.71%). Therefore, we can conclude that both methods and techniques of oral hygiene and brushing should adapt to the specific needs of children under five